IMPLEMENTASI SISTEM AKUNTANSI KEUANGAN PEMERINTAH DAERAH DALAM PENGELOLAAN LAPORAN KEUANGAN PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KOTA DENPASAR - Ni Luh Putu Sandrya Dewi; Ida Ayu Nyoman Yuliastuti (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2019)
The financial statements of local governments can meet qualitative criteria, including: understandable, relevant, reliable, and comparable, regardless of the influence of the application of adequate local government financial accounting systems. So, it is important that this research is conducted to analyze the implementation of the financial accounting system for the management of financial statements. This research has conducted a survey in the form of a questionnaire to 47 respondents who were employees of the Regional Financial and Asset Management Agency of the City of Denpasar. The results of this study indicate that the financial accounting system and local government financial reports in the Regional Financial and Asset Management Agency of the City of Denpasar are in good category. The application of local government financial accounting systems has a correlation with the management of financial statements. All human resources in the Regional Financial and Asset Management Agency of the City of Denpasar should understand the application of the regional government financial accounting system, so that quality financial statements can be realized and meet the common goals.